A Simulation Study on the Variation of Thermospheric O/N2 With Solar Activity. Issue 6 (20th June 2022) - Li, Zhongli; Luan, Xiaoli; Lei, Jiuhou; Ren, Dexin
Abstract: The ratio of number density of atomic oxygen (O) to that of molecular nitrogen (N2 ) in the thermosphere (O/N2 ) on the constant pressure surface, which has complex temporal and spatial characteristics, is widely regarded as an important parameter connecting the terrestrial thermosphere and daytime ionosphere. Previous studies demonstrated that the thermospheric O/N2 increases with increasing solar activity, and the changes in O/N2 with solar activity show significant difference between winter and summer hemispheres. However, the root causes, which are responsible for the solar activity variation of O/N2, are not fully understood. In this study, the contributions of various physical and chemical processes on the response of O/N2 to the solar radiation change were quantitatively investigated through a series of controlled simulations from the Thermosphere Ionosphere Electrodynamics General Circulation Model. The simulation results suggested that the chemical processes lead to the increase of thermospheric O/N2 over the globe with increasing solar activity. The increase of O/N2 with solar activity is dominated by the enrichment of O abundance and the loss of N2 abundance in the lower and upper thermosphere, respectively. Moreover, the simulation results suggested that the stronger hemispheric asymmetry is attributed to the stronger thermospheric circulation, which changes the vertical advection of O/N2 through both direct and indirect effects. Key Points: The chemical processes which change O and N2 abundances are mainly responsible for the increase of thermospheric O/N2 with solar activity The solar activity dependence of O/N2 is attributed to the enrichment of O and loss of N2 in the lower and upper thermosphere, respectively The variation of hemispheric asymmetry of O/N2 at solstice with solar activity is associated with the changes in thermospheric circulation